The Effectivity Of Juwet (Syzygium Cumini) Leaf Ethanolic Extract In Rabbit’s Wound Healing - Miranda Susanti Putri (Universitas STRADA Indonesia, 2023)
Medical plant which has fewer side effects than chemical drugs, is used by people as an alternative to treat wound. Juwet as a medicinal plant has the potential to be developed as a wound healer. The purpose of this study was to determine the ability or activity of juwet leaf extract (Syzygium cumini) in wound healing. The test was carried out using New Zealand rabbits by making wounds on the rabbit's back which were then divided into 5 treatment groups. The treatment group consisted of Group I given aquadestilata, Group II given povidone iodine, Group III given 25% juwet leaf extract, Group IV given 50% juwet leaf extract, and Group V given 75% juwet leaf extract. The results showed that juwet leaf extract (Syzygium cumini) affected wound healing. Average wound diameter consecutively 6,69±1,34, 5,79±2,19, and 4,50±1,70 on day-7. 0,70±0,99, 0,46±0,65, and 0,00±0,00 on the day-10. Based on the results of the research conducted, it can be concluded that juwet leaf extract (Syzygium cumini) has a wound-healing effect on rabbits and the best concentration of juwet leaf extract (Syzygium cumini) for wound-healing activity is 75%.